Agricultural Sustainability in Indonesia: The Role of Energy, Technology, Markets, and Institutions - Darmawanto Uria; Trees Augustine Pattiasina; Yohanes Kamakaula (West Science Social and Humanities Studies, 2026)
This study investigates the transformation of environmentally friendly agriculture in Indonesia by analyzing the impact of renewable energy use, precision agriculture technology, market access, and institutional support on agricultural sustainability outcomes. A quantitative approach was employed using primary data collected from 85 respondents through a structured questionnaire measured on a five-point Likert scale. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 4) to examine both direct and indirect relationships among variables. The results indicate that renewable energy use, precision agriculture technology, market access, and institutional support all have significant positive effects on sustainability outcomes. Institutional support also shows strong influence on the adoption of renewable energy and precision agriculture. Furthermore, market access partially mediates the relationship between technological adoption and sustainability outcomes. The model demonstrates strong explanatory power, indicating that the integration of technological, economic, and institutional factors plays a crucial role in driving sustainable agricultural transformation. This study provides practical implications for policymakers and stakeholders in designing integrated strategies to enhance agricultural sustainability in Indonesia.